Academic Cooperation between Africa, Asia and Latin America: The Place of diasporas - Woldegiyorgis, Ayenachew A.; Luchilo, Lucas; Pham, Thanh (International Journal of African Higher Education, 2022)
Interest has grown in the role of diaspora in advancing higher education and scientific research as academic mobility continues to generate more transnational communities a with high educational profile. The academic literature is picking up on how diasporas and their organisations facilitate academic and research collaboration between institutions in their ‘host’ and ‘home’ countries. However, this discourse largely focuses on those residing in industrialised countries, particularly Europe and North America. There is limited research on the diasporic relationship between and within regions in the Global South, and even less on diaspora mediated academic collaboration between Africa, Asia and Latin America. Against this backdrop, this article explores the role of diaspora in academic and scientific collaboration within and between these regions. It highlights some historical and contemporary migratory relations between them, along with student mobility as a means of formation of academic diaspora. The article argues that, among other things, the limited academic collaboration between countries of the Global South can be attributed to structural issues such as inequality in the geopolitics of knowledge and the characteristics of migrant communities. It also suggests possible future scenarios including trends in migration and the potential to foster scientific collaboration.